Multifunctional gluten/guar gum copolymer with self-adhesion, self-healing, and remolding properties as smart strain sensor and self-powered device - Artjima Ounkaew; Pornnapa Kasemsiri; Natnaree Srichiangsa; Kaewta Jetsrisuparb; Jesper T. N. Knijnenburg; Manunya Okhawilai; Salim Hiziroglu; Somnuk Theerakulpisut (eXPRESS Polymer Letters)
In this research, a multifunctional strain sensor based on gluten/guar gum (GG) copolymer was developed. The effects of gluten/GG blended ratios on the mechanical and electrical properties, self-adhesion, self-healing, remolding, selfpowered and long-term stability of the strain sensors were studied. Among tested substrates, the gluten/GG blend indicated a strong adhesion to wood and paper substrates and showed a maximum adhesive strength at 1.5 wt% of GG in the copolymer (gluten/GG-1.5%). The adhesive strength of gluten/GG-1.5% decreased in the acceptable range when it was applied in 10 repeated adhesion cycles. The gluten/GG-1.5% exhibited a high electrical conductivity of 0.12 S/m and stretchability of 465%. The gluten/GG-based sensor containing glycerol showed long-term stability of self-healing, remolding, and self-powered ability when stored for 7 days, whereas the self-adhesive ability decreased with increasing storage time. The self-adhesive gluten/GG-1.5% was used to monitor human limb movements, which showed remarkable sensitivity during the storage time of 3 days. Such properties suggested a potential use of smart strain sensors with multifunctional capabilities for applications in wearable electronic devices.